The Decision to Extubate: The Association between Clinician Impressions and Objective Extubation Readiness Criteria in a Pediatric Intensive Care Unit - Marupudi, Neelima K.; Steurer-Muller, Martina; Franzon, Deborah (Journal of Pediatric Intensive Care, 2022)
Objective Objective tools such as spontaneous breathing trials (SBT) aim to identify patients ready for extubation and shorten the length of mechanical ventilation (MV). Despite passing an SBT, patients sometimes are not extubated based on clinicians' subjective impressions. In this article, we explored the factors that influence the decision to extubate among pediatric intensivists and their association with objective criteria.Design This is a single-center prospective observational study.Setting This study was conducted in an academic, multidisciplinary 20-bed pediatric intensive care unit (PICU).Patients The study group involves mechanically ventilated, orally intubated patients admitted to the PICU from January 1 to June 30, 2019.Measurements and Main Results Objective clinical data were collected for 650 MV days. Attending surveys about extubation readiness were completed for 419 (64.5%) MV days and 63 extubation events. Extubation occurred on 42% of days after passing an SBT. The primary reasons patients who passed an SBT were not extubated on days were unresolved lung pathology (66.6%) and fluid overload (37.6%). On days without extubation, there was no association between a specific reason for not extubating and SBT result (p > 0.05).Conclusions In this single-center study, the decision to extubate was not strongly associated with passing an SBT, indicating that clinician impressions, namely unresolved lung pathology and fluid overload, outweighed objective measures for determining extubation readiness. To mitigate morbidities and costs associated with unnecessarily prolonged intubations, a better-defined extubation readiness process is needed to guide the decision to extubate in the pediatric population.
Keywords: Extubation; mechanical ventilation; spontaneous breathing trial; reintubation; PICU